Information environment, market-wide sentiment and IPO initial returns: Evidence from analyst forecasts before listing - Hongjun Zhu; Cheng Zhang; He Li; Shimin Chen (China Journal of Accounting Research, 2015)
Measuring the information environment of firms using analyst (price) forecast bias and forecast dispersion before listing, we empirically examine the interactive influence of the information environment and market-wide sentiment on the initial returns of initial public offerings (IPOs). We find the smaller the analyst forecast bias/dispersion, the lower the effect market-wide sentiment has on IPO initial returns. This finding indicates that information asymmetry is a basic reason for noise trading occurs and demonstrates the positive effect of financial analysts during IPOs. In addition, the effect of analyst forecasts is more pronounced during periods of rising markets and when IPO prices are not regulated.
Keywords: G02; G14; G24; 650; Market-wide sentiment; Analyst forecasts; IPO initial return